HIV, infant feeding and more perils for poor people: new WHO guidelines encourage review of formula milk policies - Anna Coutsoudis; Hoosen M Coovadia; Catherine M Wilfert (The World Health Organization, 2008)
The release of the new WHO guidelines on HIV and infant feeding, in a global context of widespread impoverishment, requires countries to re-examine their infant-feeding policies in relation to broader socioeconomic issues. This widening scope is necessitated by compelling new reports on the scale of global underdevelopment in developing countries. This paper explores these issues by addressing feeding choices made by HIV-infected mothers and programmes supplying free formula milks within a global environment of persistent poverty. Accumulating evidence on the increase in malnutrition, morbidity and mortality associated with the avoidance or early cessation of breastfeeding by HIV-infected mothers, and the unanticipated hazards of formula feeding, demand a deeper assessment of the measures necessary for optimum policies on infant and child nutrition and for the amelioration of poverty. Piecemeal interventions that increase resources directed at only a fraction of a family's impoverishment, such as basic materials for preparation of hygienic formula feeds and making flawed decisions on choice of infant feeding, are bound to fail. These are not alternatives to taking fundamental steps to alleviate poverty. The economic opportunity costs of such programmes, the equity costs of providing resources to some and not others, and the leakages due to temptation to sell capital goods require careful evaluation. Providing formula to poor populations with high HIV prevalence cannot be justified by the evidence, by humanitarian considerations, by respect for local traditions or by economic outcomes. Exclusive breastfeeding, which is threatened by the HIV epidemic, remains an unfailing anchor of child survival.